Impact of Urbanization to an Island and the Continent: Species Turnover and Nestedness in Neotropical Bird Assemblages - Caula, Sabina A.; Sanz D'Angelo, Virginia (Frontiers in Ecology and Evolution, 2021)
Islands are well known as particular and vulnerable ecosystems with evolutionary histories, environmental characteristics, and original communities different from those of continents. On the contrary, urban environments are recent, artificial, and structurally similar among distant regions. To assess the relative importance of regional and local processes on urban biota we chose two urban environments, one on the mainland, and another on an island in the same ecoregion. We asked whether the urbanization process affects the inland’s avian biodiversity in the same way as in the continent. We defined an urban gradient with three levels of building density: patches of native vegetation (remnant woodlands in the urban matrix), medium density urbanized areas that maintain vegetation along the streets and gardens, and residential areas with little vegetation cover and higher building density. In each geographic locality, we selected three sites (replicates) for each level of the urban gradient and did bird surveys. We found twice as many species in the urban landscape of the continent (69) as on the island (35), with analogous richness decrease along the gradient in both regions. Species similarity was higher between urbanized sites of both regions compared with the similarity between woodlands and urbanized sites, showing that urban matrix filters similar species of each pool regionally. Individual species responded to urban structure in different ways. We found 32% urban exploiters, 48% urban tolerant, and 20% urban avoiders bird species in both regions. However, some species showed different frequencies of occurrence on the island and the continent. Species turnover contributed more than richness differences to species dissimilarity along the urban gradient on the continent. Contrarily, the nestedness component (species being a strict subset of the species at a richer site) was higher on the island. We concluded the negative impact of highly urbanized areas on birds was stronger on the island than on the continent. Our results may help to assess the implications of beta diversity loss, especially on islands.